2013
DOI: 10.1159/000353975
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Outcome of Conventional in vitro Fertilization and Intracytoplasmic Sperm Injection in Moderate Male Infertility from Ejaculate

Abstract: Objective: To evaluate whether couples with moderate male infertility should be treated with conventional in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Patients and Methods: A total of 249 couples with moderate male infertility undergoing their first IVF/ICSI cycle were enrolled in the study. The couples were divided into two groups according to the results of semen analysis: moderate oligozoospermia (O group) and moderate oligoasthenozoospermia (OA group). Sibling oocytes were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Moreover, important numbers of former cryptorchid patients are still being reported in the adult literature to be infertile despite successful orchidopexy [20] . In male factor infertility, pregnancy may be achieved by the use of assisted reproductive technology with limited success; however, the cost of male factor infertility treatment markedly exceeds the total cost of LHRHa treatment of a cryptorchid boy [19,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, important numbers of former cryptorchid patients are still being reported in the adult literature to be infertile despite successful orchidopexy [20] . In male factor infertility, pregnancy may be achieved by the use of assisted reproductive technology with limited success; however, the cost of male factor infertility treatment markedly exceeds the total cost of LHRHa treatment of a cryptorchid boy [19,21] .…”
Section: Discussionmentioning
confidence: 99%
“…A sibling oocyte RCT of IVF versus ICSI for couples undergoing their first treatment for moderate oligozoospermia failed to reveal any difference in pregnancy rates. 34 This was confirmed by a further RCT on patients attending their first IVF treatment for the same indication. 35 However, although research does not currently support the routine use of ICSI for even moderate degrees of oligozoospermia, substantial practice variations exist, with some laboratories routinely performing ICSI for every case of suspected male infertility.…”
Section: Semen Analysismentioning
confidence: 70%
“…The decision of the best treatment option is more difficult in case of moderate oligozoospermia or oligoasthenozoospermia [ 106 ]. Shuai and colleagues demonstrated that moderate oligoasthenozoospermia does not negatively affect c-IVF clinical outcomes, such as fertilization, implantation and pregnancy rates, compared to ICSI treatment.…”
Section: Conventional Ivf and Male Gametesmentioning
confidence: 99%